2022
DOI: 10.1111/jfbc.14297
|View full text |Cite
|
Sign up to set email alerts
|

Dietary olive oil enhances the oral tolerance of the food allergen ovalbumin in mice by regulating intestinal microecological homeostasis

Abstract: Increasing evidence indicates that intestinal microecological imbalances are strongly associated with food allergen intolerance. This study investigated the effect of olive oil on food allergy susceptibility and intestinal microecology based on an ovalbumin (OVA)‐sensitized mouse model. The results indicated that the allergic symptoms of sensitized mice were alleviated when they were supplemented with olive oil at 1–3 g/kg per day for 7 weeks. Intestinal epithelium observation showed repaired ileum villi and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…All the animal studies indicated a positive relationship between the food components of the MD and food allergies. The food components used were olive oil and enriched polyphenols [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All the animal studies indicated a positive relationship between the food components of the MD and food allergies. The food components used were olive oil and enriched polyphenols [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…All four animal studies used the ovalbumine (OVA)-sensitized BALB/c mouse model as their food allergy model. The two studies by Ma et al (2022Ma et al ( , 2023 fed their animals olive oil prior to sensitization. In the studies by Singh et al and Zuercher et al [23,24], they fed their mice with enriched polyphenols (either epicatechin or flavonol).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was shown that olive oil confers protection again food allergies by improving gut mucosal barrier integrity [79]. Olive oil also enhances oral tolerance to dietary allergens by decreasing serum antigenspecific IgE, antigen-specific IgG, and histamine [80]. Increased IL-10 and decreased IL-4 associated with olive oil feeding indicate that Tregs and Bregs are induced.…”
Section: Dietary Lipidsmentioning
confidence: 99%